Local Factors Influencing Alveolar Healing Process - Menezes Júnior, Laerte Ribeiro (2009)
Although the trend of modern dentistry in search of dentist’s surgeon consciousness and their patients, aiming the tooth preservation, the tooth extraction is still a routine procedure in the exercise of dentistry. After the extraction, in the place (alveolus), it is created a surgical wound, that will be repaired by the own organism. This repairing obeys a chronological sequence, in which the neoformaded bone must be capable to support the new chewing stimulations. This work aim to show, through a literature review, the diversity of local factors that may influence the time of repairing process sequence of the alveolar wound, so the dentist surgeon knows how to act on the daily pre and trans-operatory and give a better postoperative for the patient.